2020
DOI: 10.1016/j.ijcha.2020.100619
|View full text |Cite
|
Sign up to set email alerts
|

Extent and characteristics of carotid plaques and brain parenchymal loss in asymptomatic patients with no indication for revascularization

Abstract: Highlights Age and fibrocalcific carotid plaques are associated with lower total brain volume. Fibrocalcific carotid plaques are associated with lower gray matter volumes. White matter volumes are associated with the extent of carotid atherosclerosis. Grey and white matter likely have differential susceptibility to processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…While the presence of carotid atherosclerosis does not necessarily translate into an event of ischemic stroke, the presence of carotid atherosclerosis increases the risk of ischemic stroke by 20% [ 100 ]. The presence of carotid plaques has also been associated with cerebral atrophy and reduced cognitive ability [ 101 ]. In turn, while more than a third of patients with NAFLD sufferred from carotid atherosclerosis, only 5.04% (95% CI, 2.74–9.09%) of patients with NAFLD suffered from a stroke with twice the risk (OR, 1.88; 95% CI, 1.23–2.88; P =0.02) compared to those without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of carotid atherosclerosis does not necessarily translate into an event of ischemic stroke, the presence of carotid atherosclerosis increases the risk of ischemic stroke by 20% [ 100 ]. The presence of carotid plaques has also been associated with cerebral atrophy and reduced cognitive ability [ 101 ]. In turn, while more than a third of patients with NAFLD sufferred from carotid atherosclerosis, only 5.04% (95% CI, 2.74–9.09%) of patients with NAFLD suffered from a stroke with twice the risk (OR, 1.88; 95% CI, 1.23–2.88; P =0.02) compared to those without NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, with the decrease of perfusion and alteration of morphology in cortical areas, the decrease in the volume of brain regions (mainly gray matter) involved in multisensory vestibular processing is a significant event in the development of PPPD [6,10]. CAS is independently associated with CSVD and the reduction in gray matter volume especially in cortical areas [41,42]. This might be due to the high metabolic requirements of gray matter and its susceptibility to factors that affect the regulation of CBF [42].…”
Section: Casmentioning
confidence: 95%
“…On the other hand, these potential risk factors of PPPD (hypertension, CAS, WMHs and LI) may be interactive during some pathological processes, including blood-brain barrier dysfunction and endothelial dysfunction during the occurrence and development of PPPD [50][51][52]. It was observed that CAS was positively related to the occurrence and severity of WMHs [42]. The possible interaction among different potential risk factors in the development of PPPD deserves further investigation.…”
Section: Possible Interaction Among Different Potential Risk Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, many epidemiological studies have shown the link between ARHL and AD associated with the loss of the brainstem and cerebellar volume [ 25 ]. Moreover, this biomarker has been established for various cardiovascular and cerebrovascular pathologies, including congenital heart disease, stroke and carotid stenosis [ 24 , 26 , 27 ].…”
Section: Introduction: Alzheimer’s Disease—etiology and Pathophysiologymentioning
confidence: 99%